World History, A New Perspective - Ponting, Clive (London Pimlico, 2001)
Starting from the assumption that the human story has to be seen in the round, this history examines the evolution of humans, their lives as hunters and gatherers and their eventual adoption of agriculture, before looking at the emergence of civilization across the globe.
Include Map and Index
Keywords: World history